Dangerous Integral

Calculus Level 3

e e e d x x ( log x ) ( log log x ) ( log log log x ) 4 3 = ? \large \int_{e^{e^e}}^\infty \frac {dx}{x(\log x)(\log\log x)(\log \log\log x)^\frac 43} = ?


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Chew-Seong Cheong
Jan 31, 2018

Let u = log log log x u = \log \log \log x . Then we have:

log log log x = u log log x = e u log x = e e u x = e e e u when x = e e e , u = 1 ; x = , u = . d x = e e e u e e u e u d u \begin{aligned} \log \log \log x & = u \\ \log \log x & = e^u \\ \log x & = e^{e^u} \\ \implies x & = e^{e^{e^u}} & \small \color{#3D99F6} \text{when } x=e^{e^e}, \ u=1; \ x = \infty, \ u = \infty. \\ dx & = e^{e^{e^u}} e^{e^u} e^u \ du \end{aligned}

Therefore,

I = e e e e d x x ( log x ) ( log log x ) ( log log log x ) 4 3 = 1 e e e u e e u e u e e e u e e u e u u 4 3 d u = 1 u 4 3 d u = 3 u 1 3 1 = 3 \begin{aligned} I & = \int_{e^{e^{e^e}}}^\infty \frac {dx}{x(\log x)(\log \log x)(\log \log \log x)^\frac 43} \\ & = \int_1^\infty \frac {e^{e^{e^u}} e^{e^u} e^u}{e^{e^{e^u}} e^{e^u} e^u u^\frac 43} du \\ & = \int_1^\infty u^{-\frac 43}\ du \\ & = -3 u^{-\frac 13}\ \bigg|_1^\infty \\ & = \boxed{3} \end{aligned}

We want to calculate the integral

I = e e e d x x ( log x ) ( log log x ) ( log log log x ) 4 / 3 , I = \int _{ { e }^{ { e }^{ e } } }^{ \infty }{ \frac { dx }{ x\left( \log { x } \right) \left( \log { \log { x } } \right) { \left( \log { \log { \log { x } } } \right) }^{ 4/3 } } },

where log ( x ) \log(x) stands for the natural logarithm of x x . For that we may use the substitution u = log ( x ) u = \log (x) and therefore d u = d x / x du = dx/x , so

I = e e d u u ( log u ) ( log log u ) 4 / 3 . I = \int _{ { e }^{ e } }^{ \infty }{ \frac { du }{ u\left( \log { u } \right) \left( \log { \log { u } } \right)^{4/3} } }.

Under a new substitution v = log ( u ) v = \log(u) we have

I = e d v v ( log v ) 4 / 3 . I = \int _{ { e } }^{ \infty }{ \frac { dv }{ v \left( \log { v } \right)^{4/3} } }.

Finally, if y = log ( v ) y = \log(v)

I = 1 d y y 4 / 3 = ( 3 y 1 / 3 ) 1 = 3. I = \int _{ { 1 } }^{ \infty }{ \frac { dy }{ y^{4/3} } } = \left(- \frac{3}{y^{1/3}} \right)_1^\infty = 3.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...